Financial Feasibility of Timber Harvesting Under Conventional and Sustainable Forest Management in a Timber Concession in Terengganu - Mat, Salleh (2006)
One of the issues in forest management was the implementation of the Malaysian Criteria and Indicators (MC&I). This would increase the cost of forest harvesting (timber harvesting) and affect the concessionaire’s profit. The study was framed to study the options of forest harvesting “with sustainable forest management (wSFM)” and “without sustainable forest management (woSFM)”. The benefit and cost (BCA) analysis was used to determine the difference in benefit between the option wSFM and the option woSFM of a long-term forest concession. The results of the study show that the costs of forest harvesting with sustainable forest management were higher than those without sustainable forest management by a total of 44.36% or RM2,418.22/ha (RM86.34/m3). The average harvesting costs of non-timber forest products (NTFPs) such as bamboo and rattan were RM302.62/ha and RM77.23/ha respectively. In wSFM, costs increased by about 49.55% for the concessionaire and 28.20% for the logging contractor. The net benefit or net present value (NPV) of wSFM (timber + bamboo + rattan) was 38.09% lower compared with woSFM (timber only). In wSFM, compared with woSFM, the concessionaire lost a benefit of about 7.00%, the logging contractor gained an additional benefit of 6.00% and the government 1.00%. The total benefit gained with sustainable forest management was less compared with that without sustainable forest management, timber harvesting with sustainable forest management was profitable. Forest harvesting with and without sustainable forest management was viable at 10% interest rate in 60 years cutting cycle. The concessionaire received the highest net benefit compared with the logging contractor and the government in forest harvesting with and without SFM